Sustainable change agency in an indigenous community - Pavlova, Anisiya (2023)
Global economic development has led to sustainability challenges, particularly evident in the adverse effects of climate change on vulnerable communities worldwide. In response to this urgent global crisis, there is a pressing need for diverse approaches to studying sustainability transitions for effective mitigation and adaptation strategies. This thesis explores the influence of traditional beliefs and heritage on sustainability agency formation in the Sakha Republic. By integrating indigenous knowledge into sustainability science and addressing the limited research on sustainability activism in Yakutsk, the paper examines environmental activism and individual agency formation within the Sakha community. Interviews with nine environmental activists from Yakutsk highlight their personal motivation for sustainable development and how they have influenced their community through activism. Traditional Sakha beliefs, centred around respect for nature, have significantly shaped respondents' perception of sustainability and driven their agency formation. The interviewees have good insight on the situation concerning major environmental and social issues in their republic, which have been described as: (1) lack of transparent economic development with sustainability in its core, (2) risks coming from permafrost thaw due to climate change, (3) low quality of life, (4) excessive exploitation of natural resources, (5) lack of influence on governmental decision-making, (6) bad air quality in summers and forest fires, and, finally, (7) political situation in the country. Globaali talouskehitys on johtanut kestävän kehityksen haasteisiin, jotka ilmenevät ilmastonmuutoksen haitallisina vaikutuksina haavoittuville yhteisöille maailmanlaajuisesti. Tämän maailmanlaajuisen kriisin vuoksi tarvitaan kipeästi erilaisia lähestymistapoja kestävyyden muutoksen tutkimiseen, tehokkaiden lieventämis- ja sopeutumisstrategioiden aikaansaamiseksi. Tämä opinnäytetyö tutkii perinteisten uskomusten ja perinnön vaikutusta kestävän toimijuuden ...